NOTA ACERCA DE ALGUNAS ESAN LUIS POTOSIECIES DE ROEDORES DE LOS GENEROS DIPODOMYS PEROGNATHUS Y PEROMYSCUS - VILLA RAMIREZ, BERNARDO (My University, 1941)
In the systematic and descriptive study of the rodents belonging to the genera Dipodomys, Perognathus and Peromyscus in the collections of the Section of Mastozoology and Comparative Anatomy of the Inst of Biology, most of them collected in the northern
ANS INST BIOL
Keywords: NOTA, ESPECIES, ROEDORES, GENEROS DIPODOMYS, PEROGNATHUS, PEROMYSCUS; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ROEDORES